Flashcard Learning Media to Improve English Vocabulary for Elementary School Students - Mela Fitania; Rahma Puspitarani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
This article aims to create new innovations in learning media so that learning in elementary schools can run effectively and improve the mastery of English vocabulary. The research method used is literature study. The research method used is a review study of books, literature, notes, and reports relating to the problem being solved. Literature sources in this study were obtained from books, journals, and research results. This research includes the process of identifying theories systematically, finding literature, and analyzing documents that contain information related to the research topic. The result of this study is learning media that can be applied by teachers to achieve learning objectives effectively and improve the mastery of English vocabulary.